Dampak Kualitas Layanan Terhadap Kepuasan Masyarakat: Sebuah Studi Pada Layanan Publik Pedesaan - Muhammad Ali Aqsa (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This applied research study, conducted using a survey method, aimed to analyze the impact of service quality on community satisfaction within the context of rural public services. A total of 88 respondents participated in the study, which was carried out at a village office. The collected data were analyzed using a t-test and coefficient of determination analysis. The t-test results confirm that service quality has a significant and positive effect on community satisfaction (t-statistic = 11.128 > t-table = 1.988, with a significance level of p < 0.05). Furthermore, subsequent analysis revealed a strong relationship between the two variables, indicated by a correlation coefficient of 0.768. More specifically, service quality was found to contribute 59.0% (R Square = 0.590) to the variation in community satisfaction levels. This study concludes that in the rural public service context, service quality is a dominant determining factor in shaping community satisfaction.